Ecuador’s Yasuní-ITT Initiative : A Study of Diplomatic Failure and Systemic Challenges in International Environmental Diplomacy - Palacios, Antonella; Lisa, Aleš, 1956-; Costa Jordao, Ticiano; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the diplomatic failure of Ecuador’s Yasuní-ITT Initiative— an ambitious proposal to refrain from oil extraction in one of the world’s most biodiverse regions in exchange for international financial compensation. Using a qualitative case study approach, it explores the systemic, strategic, and normative challenges that contributed to the initiative’s collapse. Drawing from constructivist, neo-realist, and climate justice perspectives, this preliminary study situates Ecuador’s proposal within the broader tensions of international environmental diplomacy. The study argues that the initiative failed not only due to limited donor support but also because of a deeper misalignment between Ecuador’s moral discourse and the structural logic of global climate governance. This discourse was grounded in the principles of Buen Vivir, ecological debt, and post-extractivism. This preliminary research incorporates primary sources, policy documents, and two semi-structured interviews with key actors from both civil society and the state. The findings suggest that internal political fragmentation, extractivist dependencies, and the rigidity of mechanisms like REDD+ and the Clean Development Mechanism (CDM) undermined Ecuador’s credibility and strategic position. Drawing on comparative insights from Costa Rica’s ecotourism model and Norway’s REDD+ diplomacy, the thesis concludes that the Yasuní-ITT case highlights the systemic barriers facing Global South-led climate innovation within a largely transactional and power-driven diplomatic system.
Vedoucí práce: Aleš Lisa
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses